Tinjauan Etika Bisnis Islam pada Penetapan Upah Jasa Angkut Barang di Terminal - Jamaluddin Burhanudin (UPT Publikasi Ilmiah Unisba, 2023)
as well as permissible and unlawful in muamalah activities, are known as Islamic business ethics. The principles of unity, balance, free will, responsibility, truth: Virtue and honesty are Islamic principles that must be prioritized in the Islamic economic system because they are very important aspects in the business activities of a business actor. In this research, the type of research used is the research method of library research and field research with a qualitative approach. The use of this approach is adapted to the main objective of the research, which is to describe and analyze the practice of goods transportation services at the Cicaheum terminal. It can be concluded that the tariff for goods transportation services at the Cicaheum Terminal depends on the transportation service users who will provide wages to the goods transportation service officers. Negotiations often occur between officers and users of goods transportation services regarding how much the tariff is for using goods transportation services, which refers to how much and the weight of the goods to be carried. The application of wages for goods transportation services at the Cicaheum terminal does not meet the principles of business ethics, because in determining the wages the transportation service officers do not explain clearly and in detail the wage system for goods transportation services. Etika bisnis Islam mengacu pada aturan tentang hal-hal yang boleh dan tidak boleh dilakukan, serta halal dan haram. Prinsip-prinsip seperti kesatuan, keseimbangan, kehendak bebas, tanggung jawab, dan kebenaran harus menjadi prioritas utama dalam sistem ekonomi syariah. Karena kebajikan dan kejujuran merupakan prinsip Islam yang harus diutamakan karena merupakan komponen yang sangat penting dalam aktivitas bisnis seorang pelaku usaha, mereka harus memprioritaskan keduanya. Tujuan utama penelitian adalah untuk memberikan penjelasan dan analisis tentang prosedur yang digunakan oleh jasa pengangkut barang di terminal Cicaheum. Jenis penelitian yang digunakan adalah studi kepustakaan dan lapangan kualitatif. Dapat di simpulkan bahwa tarif jasa angkut barang di Terminal Cicaheum itu tergantung pengguna jasa angkut yang akan memberikan upah kepada petugas jasa angkut barang. Sering terjadi negosiasi antara petugas dan pengguna jasa angkut barang mengenai berapa tarif menggunakan jasa angkut barang yang mengacu kepada berapa banyak dan berat barang yang akan dibawa. Penerapan upah jasa angkut barang diterminal Cicaheum kurang memenuhi prinsip etika bisnis, karena dalam penetapkan upah petugas jasa angkut tidak menjelaskan secara jelas dan rinci sistem upah jasa angkut barang.